PENGEMBANGAN KOMPETENSI PELAYANAN DESA BERBASIS DIGITAL DI DESA WANGUNJAYA KECAMATAN NARINGGUL KABUPATEN CIANJUR - Rohayati, Yeti; Nurdiyansah, Andri; Achmad Syam, Rifqi Zaeni (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2024)
One of the obstacles faced by the government in socializing policies or conveying performance is information and technology problems. IT is an important thing that must be considered in services during the current pandemic. Wangunjaya Village is one of the villages in Naringgul District, Cianjur Regency which is considered ready to face the digital era. One of the achievements obtained by Wangunjaya Village is the ownership of an informative website. The process involved is certainly long and involves many parties. However, there is no guarantee that the success achieved by Wangunjaya Village will continue continuously. There is a need to develop competence in the services of village officials. The aim is to increase the competence of service activities during the pandemic in digital-based services, village administration management must be managed well and increase competence, implementation and supervision when handling a pandemic outbreak requires a special service and is followed by health protocols, even services are carried out using mobile center which is carried out using digital services online and even receiving services via telephone. Development of Digital-Based Village Service Competency in Wangunjaya Village, Naringgul District, Cianjur Regency is able to improve the quality of village apparatus resources and service competency in providing services to the community during the current pandemic. Especially services related to village administration and health services to the community during the Covid-19 pandemic.